(untitled) (FUDMA JOURNAL OF SCIENCES, 2020)
This study aimed at examining the trend analysis of monthly and annual rainfall profile in Katsina and its environs. The specific objective was to determine the monthly and annual trends in rainfall for the area. Rainfall data from 1971 to 2010 was sourced from the archive of the Nigerian Meteorological Agency (NiMets) Katsina Airport. The data was used to characterize rainfall trends for monthly and annual total which are the determinants of rainy season using Microsoft excel tool (2016) and SPSS 23.0 version. The 5-year running mean showed that below average rainfall was experienced from the early 1970s up to 2000. Findings also showed that above average rainfall is being experienced from the year 2000 afterward. Findings further indicated that there was a significant decrease in rainfall amount in the month of June, little change in the month of July and substantial increase in the months of August and September. The study concludes that there is an apparent increase in rainfall amounts in recent years. The study recommends that there is need to improve information delivery and foster the use of climate information to inform decision making, using seasonal climate forecasts to inform farmers and other stakeholders to avoid surprises by taking right decisions. Additional functioning synoptic weather stations should be provided to complement the existing ones in the study area with distance from each other not more than 100km to conform with WMO standard. This will enhance network of data collection and accurate seasonal rainfall prediction.